1986
DOI: 10.1016/0014-5793(86)80095-3
|View full text |Cite
|
Sign up to set email alerts
|

Poliovirus‐encoded proteinase 3C: a possible evolutionary link between cellular serine and cysteine proteinase families

Abstract: Here we demonstrate significant similarities between the amino acid sequences of trypsin (a serine protease) and the N-terminal piece of a specific fragment of the poliovirus polyprotein encompassing the sequence of the viral proteinase 3C, and also between cathepsin H (a cysteine protease) and the C-terminal piece of the same fragment. A coherent alignment of the sequences of the 3 proteases was obtained, in which the principal catalytically active residues occupy identical positions. A hypothesis is proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 46 publications
0
51
0
Order By: Relevance
“…The similarity of sequence stretches surrounding the (putative) catalytic Cys residues of 3C Pr° to those around the catalytic Ser of chymotrypsin-like proteases has been noticed and discussed previously [11]. These observations prompted a further, more detailed comparison between the two enzyme families.…”
Section: Comparison Of 3c Pr° and Chymotrypsin-like Proteasesmentioning
confidence: 55%
See 2 more Smart Citations
“…The similarity of sequence stretches surrounding the (putative) catalytic Cys residues of 3C Pr° to those around the catalytic Ser of chymotrypsin-like proteases has been noticed and discussed previously [11]. These observations prompted a further, more detailed comparison between the two enzyme families.…”
Section: Comparison Of 3c Pr° and Chymotrypsin-like Proteasesmentioning
confidence: 55%
“…Due to the different location of the (putative) catalytic Cys residues and to the lack of overall sequence similarity, it was suggested that 3C-like proteases were not evolutionarily related to other cysteine proteases [5], their formal analogy being explained by convergence. The considerable similarity between the regions of 3C proteases around the putative catalytic Cys to those surrounding the catalytic Set of chymotrypsin-like proteases noticed by us [10,11] was also attributed to convergence [8]. Hence, the general consensus that 3C-like proteases constitute an entirely independent enzyme family.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…The peaks in fractions 40-50 contained cp N2 and cp N3 and were well resolved from the peak in fractions 51-56, which contained cp N1 . Although cp N2 and cp N3 eluted in the same general region, it was possible to resolve the majority of the cp N2 (fractions 44-47) from the cp N3 (fractions [40][41][42][43]. cp N2 was subjected to N-terminal sequence analysis by automated Edman degradation (Table I).…”
Section: Of 51 Kda (A and B Lanes 2-4)mentioning
confidence: 99%
“…The 2A proteases of rhino-and enteroviruses are small thiol proteases with structural similarities to chymotrypsin and α-lytic protease (39)(40)(41). The primary cleavage site in rabbit eIF4G is Arg 486 -Gly 487 (15), although a secondary site of unknown location has been suggested for the 2A protease of HRV2 (12).…”
mentioning
confidence: 99%